In memoriam Linnart Mäll - LÄÄNEMETS, Märt (Acta Orientalia Vilnensia, 2010)
Tartu University No one departs this world without leaving a trace. Every person or creature leaves behind a trace that is distinctive in terms of visibility, extent and influence. That trace may be ploughed into the soil of a field or carved in history by stone or the sword. It may, however, also at first glance be less noticeable but more influential than that recorded by plough, stone or sword—that is the case when the trace a person leaves is in the area of culture.